THE ROLE OF SERUM FACTORS IN ANIMAL BONE MARROW REGENERATION AFTER INRADIATION AND MYELOTRANS-PLANTATION - Romanova, E.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The influence of serum factors on bone marrow cells and haemopoesis restitution during 10-90 days after lethal irradiation of mice and myelocariocytes grafting per se and enriched by thymocytes bone marrow cells was studied. The prevalence of stimulating serum factors during the stage of cellular compound restitution and after termination this period the moving positive balance to the side of suppressing factors was determined. It was established, that not only immunoglobulins has the stimulating effect on haemopoietic cells proliferation, but also factors of non-immunoglobuline nature.